Powder metallurgy compacted electrodes of electrical discharge machining for surface modification of titanium alloy (Ti-6AI-4V) - Ndaliman, Mohammed Baba (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Alpha-beta titanium (Ti-6Al-4V) alloy is the most commonly used titanium alloy. Over 70 % of all titanium alloy grades are products of the sub-grade of this alloy. It is widely used in aerospace, biomedical and corrosive environments. However, its poor abrasive and adhesive wear resistance makes it susceptible to premature failure in applications where the surface is in sliding or rolling contact with metals. Such surfaces would therefore need strengthening to prevent early service failures. Studies have shown that the wear rate of Ti-6Al-4V alloy under minimum sliding conditions (0.3m/s, 50N) is well above 10-3 mm3/m, the normal upper limit for mild wear of materials. Since electrical discharge machining (EDM) is one of the non conventional techniques used in machining this alloy, the possibility of enhancing its surface wear properties through manipulation of its (EDM) process parameters is therefore explored in this work. The conventional EDM is modified with the incorporation of a new Cu-TaC composite powder metallurgy (PM) compacted electrode and urea solution in distilled water as dielectric fluid, with the assumption that combination of elements from the electrode and dielectric would lead to formation of hard layer of nitrides and carbides on the machined surface thereby reinforcing it against wear during sliding contacts. The overall study is made up of electrode development; parametric investigation of alloy with central composite design (CCD) to determine MRR, TWR, Ra, micro-hardness (Mh) and the work surface wear rate (Wr); optimization of the models and finally, examination of the integrity of the EDMed surface in terms of SEM/EDX and XRD analysis. The first part of the study on the PM Cu-TaC electrodes indicates that they have high electrical conductivity (94.96–189.92Ω-1m-1), good thermal conductivity (29.70–33.20W/mK) and average density (6.13-9.80 g/cm3), and their machining performance also complies with the normal EDM tool characteristics. In the second segment of the investigation, models were used to relate both the machining performance measures and the modified surface outputs to the input parameters (urea concentration, peak current, pulse duration and duty factor). Validations of the models and the optimal parameters show that their prediction accuracy is within the limit of 1.3 to 8.5% prediction error. EDX spectra analyses of modified surfaces indicate the presence of Cu, Ta, Ti, C, N and O on the EDMed surface. XRD analyses revealed that compounds like Ta2N, TaC, TiC, Ti2N, TiO, C3N4 etc. are formed on the alloy surface. Furthermore, SEM micrographs indicate that combined urea concentration and peak current around the axial conditions produced the best topography with fewer micro-defects. Higher current is observed to increase the propagation of these defects. On the effect surface treatment on the alloy, the highest micro-hardness of 1794.67Hv obtained with Cu-TaC/urea dielectric fluid is equivalent to about 50% improvement over that of Cu/distilled water used for comparison. By the same comparison, about 96% reduction in surface wear rate is achieved with Cu-TaC/urea dielectric scheme. Additionally the most severe surface wear rate of 3.57 x 10-4mm3/min under Cu-TaC/urea dielectric is within the limit of mild wear of materials; with its equivalent specific wear rate of 1.52 x 10-17m3/Nm. Thus, the modified surfaces can be categorized to have attained good wear resistance state. These enhanced surface wear characteristics are achieved as a result of the hardened layer of nitrides and carbides formed on the EDMed surfaces.